THE DIFFERENCE OF SURFACE MORPHOLOGY AND CHEMICAL COMPOSITION OF SUPER-ELASTIC NICKEL TITANIUM ORTHODONTIC WIRES BEFORE AND AFTER IN ARTIFICIAL SALIVA SUBMERSION - Puspitasari, Yustisia (FKG Unlam, 2017)
Objective: In order to Investigate the difference of morphology and composition of Super-elastic NickelTitanium wire before and after submersed in artificial saliva with normal pH (pH 6:50) and acidic pH (pH3.75). Material and method: Super-elastic Nickel Titanium wire were divided into 2 groups. Each groupconsisted of 3 samples submerged in 150 ml of artificial saliva for 28 days. The first group was Super-elasticNickel Titanium wire submersed in artificial saliva with normal pH (pH 6.50) while the second group wassubmersed in artificial saliva with acidic pH (pH 3.75). Wire surface morphology was Analysed using ScanningElectron Microscope (SEM) while the wire composition was Analysed using Energy Dispersive X-raySpectroscopy (EDS. Result: Scanning Electron Microscope revealed a significant difference of surfacemorphology of super-elastic nickel titanium before and after submersed in artificial saliva between normal pH(pH 6.0) and acidic pH (pH 3.75). SEM investigation Showed a fibrous microstructure on the surface of superelasticnickel titanium before submersed in artificial saliva and became rough and showed many form of pittingor crevice corrosion after submersed in artificial saliva for 28 days. The chemical compositions in surfacemorphology were analysed using EDS Also showing a different result. The major compositions of super-elasticnickel titanium wire were the C, N, Ni and Ti and after submersed in artificial saliva for 28 days has made anyadditional elements O, Al, Si, P, Cl, Ca, K and Fe. Conclusion: the surface morphology of nickel titaniumsurface rugosity greater SEM Showed and presence of many forms of pitting or crevice corrosion aftersubmersed in artificial saliva with normal pH and acidic pH. The major surface composition of a super-elasticnickel titanium before submersed in artificial saliva were the C, N, Ni and Ti and as a major composition ofsuper-elastic nickel titanium before and after submersed in artificial saliva with normal pH (pH 6.0) and acidicpH (pH 3.75 ).